Impact of a digital mindfulness meditation service on variables related to individual causes of university dropout (2023)
This thesis delves deeply into the causes and solutions associated with university dropout in Colombia while concurrently exploring the global benefits of mindfulness meditation. Recognizing a synergy between these domains, a digital mindfulness meditation service was conceived and implemented, characterized by its free access, which aims to scale up to achieve self-sustainability in the future. Building on this foundation, two subsequent research endeavors were undertaken to gauge the effects of mindfulness meditation on university students. Specifically, individual variables previously linked to university dropout were assessed. The outcomes of these investigations shed light on the potential of mindfulness practices to impact factors contributing to academic discontinuation, presenting a novel approach to enhancing student retention and overall well-being. This thesis is organized into the following chapters: (1) An overview of Colombia's university dropout issue, research aims, and academic contributions. (2 and 3) Thesis Background: Exploring university dropout and mindfulness meditation practices. (4) A systematic literature review using the Kitchenham method that explores dropout causes, solutions, and intervention effectiveness. (5) A systematic literature review examining mindfulness meditation's potential benefits on university students. (6) Introduction of Medita, a free digital meditation platform with a sustainable business strategy. (7) A pilot test using electroencephalography (EEG) to assess the effects of digital mindfulness meditation. (8 and 9) A quasi-experiment with 107 students that evaluates metrics related to dropout and the results of a four-week meditation program. (10) Conclusions, limitations, and future research recommendations in mindfulness and university dropout are presented.